Increased ROS Production: A Component of the Longevity Equation in the Male Mygalomorph, Brachypelma albopilosa - Criscuolo, Francois; Font-Sala, Candide; Bouillaud, Frederic; Poulin, Nicolas; Trabalon, Marie (PLOS ONE, 2010)
Background The diversity of longevities encountered in wildlife is one of the most intriguing problems in biology. Evolutionary biologists have proposed different theories to explain how longevity variability may be driven by bad genes expression in late life or by gene pleiotropic effects. This reflexion has stimulated, in the last ten years, an active research on the proximal mechanisms that can shape lifespan. Reactive oxygen species (ROS), i.e., the by-products of oxidative metabolism, have emerged as the main proximate cause of ageing. Because ROS are mainly produced by the mitochondria, their production is linked to metabolic rate, and this may explain the differences in longevity between large and small species. However, their implication in the sex difference in longevity within a species has never been tested, despite the fact that these differences are widespread in the animal kingdom. Methodology/Principal Findings Mitochondrial superoxide production of hemolymph immune cells and antioxidant and oxidative damages plasma levels were measured in adult male and female B. albopilosa at different ages. We found that female spiders are producing less mitochondrial superoxide, are better protected against oxidative attack and are then suffering less oxidative damages than males at adulthood. Conclusions/Significance In tarantulas, once reaching sexual maturity, males have a life expectancy reduced to 1 to 2 years, while females can still live for 20 years, in spite of the fact that females continue to grow and moult. This study evidences an increased exposure of males to oxidative stress due to an increase in mitochondrial superoxide production and a decrease in hemolymph antioxidant defences. Such a phenomenon is likely to be part of the explanation for the sharp reduction of longevity accompanying male tarantula maturity. This opens several fundamental research roads in the future to better understand how reproduction and longevity are linked in an original ageing model.